Epidemiology and Ecology of Severe Fever With Thrombocytopenia Syndrome in China, 2010‒2018. (17th October 2020) - Miao, Dong; Liu, Ming-Jin; Wang, Yi-Xing; Ren, Xiang; Lu, Qing-Bin; Zhao, Guo-Ping; Dai, Ke; Li, Xin-Lou; Li, Hao; Zhang, Xiao-Ai; Shi, Wen-Qiang; Wang, Li-Ping; et al.
Abstract: Background: The growing epidemics of severe fever with thrombocytopenia syndrome (SFTS), an emerging tick-borne disease in East Asia, and its high case fatality rate have raised serious public health concerns. Methods: Surveillance data on laboratory-confirmed SFTS cases in China were collected. The spatiotemporal dynamics and epidemiological features were explored. The socioeconomic and environmental drivers were identified for SFTS diffusion using survival analysis and for SFTS persistence using a two-stage generalized boosted regression tree model. Results: During 2010‒2018, a total of 7721 laboratory-confirmed SFTS cases were reported in China, with an overall case fatality rate (CFR) of 10.5%. The average annual incidence increased >20 times and endemic areas expanded from 27 to 1574 townships, whereas the CFR declined from 19% to 10% during this period. Four geographical clusters—the Changbai Mountain area, the Jiaodong Peninsula, the Taishan Mountain area, and the Huaiyangshan Mountain area—were identified. Diffusion and persistence of the disease were both driven by elevation, high coverages of woods, crops, and shrubs, and the vicinity of habitats of migratory birds but had different meteorological drivers. Residents ≥60 years old in rural areas with crop fields and tea farms were at increased risk to SFTS. Conclusions: Surveillance of SFTS and intervention programs need to be targeted at areas ecologically suitability for vector ticks and in the vicinity of migratory birds to curb the growing epidemic. Abstract : This retrospective study determined the spatiotemporal patterns of severe fever with thrombocytopenia syndrome (SFTS) and socioeconomic and environmental risk drivers for its diffusion and persistence, which bridges the knowledge gap in the epidemiology and ecology of the disease. The ecological model can be used to assess risks of STFS in countries where the disease or vector ticks are emerging to guide the planning of surveillance and controls.